Penyisihan kontaminan dari air limbah hasil daur ulang baterai LiFePO4 (LFP) menggunakan penukar ion resin kation Amberlite HPR1100 Na dan resin anion Dowex Marathon A - Satryo Dewanto Suryohendrasworo; Laras Parasakti; Sarah Nabila Salma; Agus Prasetya (Jurnal Rekayasa Proses, 2021)
In 2025, it is estimated that the need for Li-ion batteries will reach 400,000 tons. Strategic efforts are needed to realize sustainable use of Li-ion batteries. After the Li-ion battery usage cycle ends, the Li-ion battery will be processed again to extract the important metals contained in the cathode, especially lithium. In general, the recycling process is carried out using a hydrometallurgical method which consists of a series of leaching and precipitation. However, in the purification process waste air is produced which contains various metals in different concentrations. For LFP batteries, these metals come from the cathode which contains Li, Na, Si, and PO4. The process of leaching and washing cathode powder requires relatively large amounts of air. Wastewater treatment resulting from the battery recycling process is expected to significantly increase water use efficiency. In this experiment, the batch adsorption method with Amberlite HPR1100 Na cation exchange resin and Dowex Marathon A anion resin was used to remove metal ions from artificial waste air. Samples of treated wastewater were taken at 3, 6, 10, 20, 30 minutes and on the 3rd day. Based on the results of the removal percentage, it was found that artificial wastewater treatment using the adsorption method using Amberlite HPR1100 Na cation ion exchange resin can reduce lithium and sodium ion levels by up to 100% in the 20th minute with variations in the adsorbent dose of 10 g/100 mL, while the use of ions Dowex Marathon A -exchange anion resin can reduce phosphate ion levels by up to 100% in the 30th minute with an adsorbent dose of 10 g/100 mL. With the adsorption isotherm, the Langmuir model is more in line with the experimental data with parameter values Qm and KL for lithium ions of 1.16 mg/g and 2.57 mg/g, sodium ions of 74.62 mg/g and 0.04 mg/g. gL/mg, and phosphate ion of 208.33 mg/g and 0.06 mg/g. In addition, kinetic studies show that the pseudo second-order model has a better fit to the data than the pseudo first-order.